Severe Diabetes Induction as a Generational Model for Growth Restriction of Rat - da Cruz, Larissa Lopes [UNESP]; Barco, Vinícius Soares [UNESP]; Paula, Verônyca Gonçalves [UNESP]; Gallego, Franciane Quintanilha [UNESP]; Souza, Maysa Rocha [UNESP]; Corrente, José Eduardo [UNESP]; Zambrano, Elena; Volpato, Gustavo Tadeu; Damasceno, Débora Cristina [UNESP] (Springer Nature, 2023)
We used uncontrolled maternal diabetes as a model to provoke fetal growth restriction in the female in the first generation (F1) and to evaluate reproductive outcomes and the possible changes in metabolic systems during pregnancy, as well as the repercussions at birth in the second generation (F2). For this, nondiabetic and streptozotocin-induced severely diabetic Sprague-Dawley rats were mated to obtain female pups (F1), which were classified as adequate (AGA) or small (SGA) for gestational weight. Afterward, we composed two groups: F1 AGA from nondiabetic dams (Control) and F1 SGA from severely diabetic dams (Restricted) (n minimum = 10 animals/groups). At adulthood, these rats were submitted to the oral glucose tolerance test, mated, and at day 17 of pregnancy, blood samples were collected to determine glucose and insulin levels for assessment of insulin resistance. At the end of the pregnancy, the blood and liver samples were collected to evaluate redox status markers, and reproductive, fetal, and placental outcomes were analyzed. Maternal diabetes was responsible for increased SGA rates and a lower percentage of AGA fetuses (F1 generation). The restricted female pups from severely diabetic dams presented rapid neonatal catch-up growth, glucose intolerance, and insulin resistance status before and during pregnancy. At term pregnancy of F1 generation, oxidative stress status was observed in the maternal liver and blood samples. In addition, their offspring (F2 generation) had lower fetal weight and placental efficiency, regardless of gender, which caused fetal growth restriction and confirmed the fetal programming influence.
Keywords: Animal models; Fetal programming; Hyperglycemia; Low birth weight; Malondialdehyde; Pregnancy